2007
DOI: 10.1016/j.neuron.2007.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning with Unstable Neural Representations

Abstract: It is often assumed that learning takes place by changing an otherwise stable neural representation. To test this assumption, we studied changes in the directional tuning of primate motor cortical neurons during reaching movements performed in familiar and novel environments. During the familiar task, tuning curves exhibited slow random drift. During learning of the novel task, random drift was accompanied by systematic shifts of tuning curves. Our analysis suggests that motor learning is based on a surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
228
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(255 citation statements)
references
References 38 publications
15
228
2
Order By: Relevance
“…Some evidence from longitudinal recordings from primary visual and somatosensory cortices supports this idea (26,38). Results from the motor cortex are more variable, with some groups reporting consistent relations between behavior and the preferred direction of single neurons (39)(40)(41) and others finding some degree of change across days (5,42) or even within the course of a single session (6). Because activity outside of the primary sensory and motor cortical areas is less tightly coupled to action in the periphery, we might expect to see more change over time in higher level association areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence from longitudinal recordings from primary visual and somatosensory cortices supports this idea (26,38). Results from the motor cortex are more variable, with some groups reporting consistent relations between behavior and the preferred direction of single neurons (39)(40)(41) and others finding some degree of change across days (5,42) or even within the course of a single session (6). Because activity outside of the primary sensory and motor cortical areas is less tightly coupled to action in the periphery, we might expect to see more change over time in higher level association areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of direct evidence, there is no reason to assume that this is the case, or more generally that stable network performance implies stable units. And indeed, both theoretical (4) and experimental results from motor cortex (5,6) demonstrate that a network composed of unstable units may nonetheless exhibit stable performance. Recent recordings from the mouse hippocampus showed that reliable location signaling is driven largely by neurons that gradually enter and leave the population of functionally active place cells over the course of several days (7).…”
mentioning
confidence: 99%
“…It was recently suggested that redundancy in the motor cortex provides robustness to noise in the system by allowing changes in neuronal activity that do not significantly affect behavior. Thus, the initial low trial-to-trial variability (which we observed) has been defined as "background" variability, which reflects a stable optimal manifold (rather than a single point) in the neuronal space in which all points produce a similar end result, but with different motor commands (Rokni et al, 2007).…”
Section: Suggested Framework For Motor Learningmentioning
confidence: 99%
“…Computational and modeling studies have put forward the intriguing idea that neuronal variability can be important for learning in general (Kirkpatrick et al, 1983;Fusi, 2002) and for motor learning in particular (Rokni et al, 2007;Fiete et al, 2007;Faisal et al, 2008). In other words, variability enables dynamic representations and continuous exploration of possible motor states and appropriate neuronal configurations that can lead to the desired state by trial and error.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies provided evidence that neural encoding properties need not be stable under all circumstances. Instead, they can change dynamically with time, both within a trial and across repeated trials (Chestek et al, 2007;Churchland and Shenoy, 2007;Rokni et al, 2007). Such changes may be attributable to changes in contextual parameters.…”
Section: Introductionmentioning
confidence: 99%